Legal Analysis of The Implementation of Restorative Justice in Domestic Violence Cases - Nora Elida Manurung; Abdul Rahman Maulana Siregar; Ismaidar Ismaidar (CV. Era Digital Nusantara, 2026)
This study aims to analyze the implementation of restorative justice in domestic violence (DV) cases from a positive legal perspective. The approach used is normative juridical, examining legislation, doctrine, and cases. Restorative justice, as an alternative to resolving criminal cases, emphasizes restoring relationships between perpetrators, victims, and the community without neglecting substantive justice. In cases of domestic violence, its implementation faces a dilemma between social recovery and protecting the rights of victims, particularly women and children. The analysis shows that the implementation of restorative justice in DV cases can only be carried out with caution, while still observing the principle of non-discrimination and the victim's right to a sense of security. The effectiveness of restorative justice in DV cases depends heavily on oversight of its implementation.